Ovire in rešitve pri sanaciji v ujmah poškodovanih zasebnih gozdov - Darja Stare (Slovenian Forestry Institute, 2020)
Frequent natural disasters in recent years have been a major challenge in private forest management and have led to increased activity among all stakeholders along the forest-wood chain. In this paper, we reviewed the literature on salvage logging in private forests damaged by natural disasters, with the aim of identifying the barriers that private forest owners face in salvaging and solutions for faster and more efficient salvaging. After reviewing the relevant literature, we included 59 articles and 25 reports in the final analysis. The results showed that researchers have not yet systematically addressed the identification of barriers. We identified 51 barriers, which we classified into 7 groups, and 68 solutions, which we classified into 11 groups. Most researchers have dealt with barriers from the 'Characteristics of private forest owners' group and solutions from the 'Stakeholder Cooperation' group. Finally, we associated the identified barriers with appropriate salvaging solutions and found that all identified solutions represent a solution for at least one of the barriers and that each barrier has at least one solution. The research represents the first, but important, step in identifying the decision-making factors for salvaging in private forests damaged by natural disasters.